Patients' Preference for Integrating Homoeopathy Services within the Secondary Health Care Settings in India: The Part 3 (PPIH-3) Study. (April 2017) - Manchanda, Rajkumar; Koley, Munmun; Saha, Subhranil; Sarkar, Debabrata; Mondal, Ramkumar; Thakur, Prosenjit; Biswas, Debjyoti; Rawat, Birendra Singh; Rajachandrasekar, Bhuvaneswari; Mittal, Renu
Indian patients' preference for integrated homoeopathy services remains underresearched. Two earlier surveys revealed favorable attitude toward and satisfaction from integrated services. The objectives of this study were to examine knowledge, attitudes, and practice of homoeopathy and to evaluate preference toward its integration into secondary-level health care. A cross-sectional survey was conducted during May to October 2015 among 659 adult patients visiting randomly selected secondary-level conventional health care setups in Kolkata, Mumbai, Kottayam, and New Delhi (India) using a self-administered 24-item questionnaire in 4 local vernaculars (Bengali, Marathi, Malayalam, and Hindi). Knowledge and practice scores were compromised; attitude scores toward integration and legal regulation were high. Respondents were uncertain regarding side effects of homoeopathy and concurrent use and interactions with conventional medicines. A total of 82.40% (95% confidence interval = 79.23, 85.19) of the participants were in favor of integrating homoeopathy services. Preference was significantly higher in Delhi and lower in Kottayam. Probable strategic measures for further development of integrated models are discussed.